2020
DOI: 10.1159/000511293
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Parameters Predict Technique Survival in Patients on Peritoneal Dialysis

Abstract: <b><i>Objective:</i></b> The incremental shuttle walking test (ISWT) is an important marker of aerobic capacity in patients on peritoneal dialysis (PD). This study aimed to evaluate its predictive value for PD-related outcomes. <b><i>Methods:</i></b> This single-center cohort study recruited outpatients on maintenance PD from our hospital between March 2017 and March 2018. Exercise capacity was assessed using measurement of ISWT and handgrip and quadriceps streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…As a result, considering multicollinearity, age, sex, CCI, eGFR, GNRI and submission rate were included as independent variables. [12][13][14][15][16][17] The same variables were selected as candidate covariates for multivariate analysis to assess their association with the secondary outcomes, peritonitis-free survival, HF-related hospitalization-free survival and ESI/TI-free survival. In addition to the standard Cox regression model for cause-specific hazards, the Fine and Grey subdistribution hazard model was used in the multivariate model as a sensitivity analysis for technique survival, 12,17 because death and transplantation were competing risk events against technique failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, considering multicollinearity, age, sex, CCI, eGFR, GNRI and submission rate were included as independent variables. [12][13][14][15][16][17] The same variables were selected as candidate covariates for multivariate analysis to assess their association with the secondary outcomes, peritonitis-free survival, HF-related hospitalization-free survival and ESI/TI-free survival. In addition to the standard Cox regression model for cause-specific hazards, the Fine and Grey subdistribution hazard model was used in the multivariate model as a sensitivity analysis for technique survival, 12,17 because death and transplantation were competing risk events against technique failure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the submission rate, variables associated with technique survival, the primary endpoint, were included in the multivariate regression. As a result, considering multicollinearity, age, sex, CCI, eGFR, GNRI and submission rate were included as independent variables 12–17 . The same variables were selected as candidate covariates for multivariate analysis to assess their association with the secondary outcomes, peritonitis‐free survival, HF‐related hospitalization‐free survival and ESI/TI‐free survival.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to E1W/E0, parameters that were previously shown to be associated with technique survival were included in the multivariate regression model. Consequently, taking multicollinearity into consideration, age, sex, CCI, eGFR, GNRI, and E1W/E0 were included as candidate-independent variables [17][18][19][20][21]. For sensitivity analyses, E0 or E1W or both was included as independent variables, instead of E1W/E0.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, continuous and extensive efforts are ongoing to identify risk factors of technique failure and to develop potential interventions to improve technique survival. Studies identified older age; male sex; diabetes mellitus; presence of comorbidities; lower residual renal function (RRF); lower nutritional status including lower body mass index, albumin, and GNRI; and lower exercise capacity assessed by the incremental shuttle walking or 6-min walking test as factors independently associated with the higher technique failure rate [17-21, 23, 24]. The present study demonstrated that E1W/E0 as readout for eosinophilic reaction at the time of PD catheter insertion was a novel marker that predicted both the higher technique failure rate and higher peritonitis and HF-related hospitalization rates in patients initiating PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation